Pengembangan Metode Pengajaran Dialogis dengan Pendekatan Hadap Masalah Paulo Freire sebagai Upaya Mewujudkan Kemerdekaan Belajar - Amalia, Shofi Nur; Sumarno, Sumarno; Fatmawati, Malinda (BRILIANT: Jurnal Riset dan Konseptual, 2024)
â€˜â€™Independence of Learningâ€ from the MBKM concept is often associated with Paulo Freire's critical pedagogy. This research and development (R&D) seek to design and test dialogic learning strategies/methods using the ADDIE model (analyze, design, develop, implement & evaluate). The product trial consisted of expert assessment and field trial through formative evaluation (one-to-one, small-group & field trial) which was conducted by 30 participants. Data collection techniques include filling out questionnairesâ€™ interviews, observation and documentation. Quantitative data analysis uses descriptive statistics with the help of IBM SPSS 26 software. The qualitative data analysis uses the help of Atlas.Tiversi 9 qualitative data analysis software. Based on the results of the field-test evaluation with a percentage of 90%, it can be concluded that the dialogical teaching method is very feasible. Three main themes from the qualitative data were (a) the relationship between the teaching method and students' responses, (b) students' readiness for critical learning and (c) the positive effects of problem-facing learning. Prospectively, our design is promising to be used as a teaching method in future MBKM curricula.